THE WELFARE STATE: MAIN PRECONDITIONS AND STAGES OF THE DEVELOPMENT IN POST-SOVIET RUSSIA - V. P. Miletsky (Дискурс)
System, sphere and structural preconditions of the development of the welfare state in the context of post-Soviet modernization of Russia are considered. Periodization of the process of the development of welfare state in modern Russia is covered and peculiarities of its main stages are considered.